حقوق المتحولين جنسيًا في ماليزيا في ضوء مقاصد الشريعة - bin hasmady, farhan; Mat Jubri@Shamsuddin, M. (Universiti Sains Islam Malaysia, 2024)
Transgenders are a marginalized group in many parts of the world including Malaysia. For this reason, some parties have demanded certain rights in favor of the transgenders. The aim of this research is to study the rights of transgender people in Malaysia from the perspective of Maqasid Syariah. The researcher has followed a set of methodologies with which he addressed the topic at hand. Using analytical approach, the researcher discussed the issue of transgenders’ rights and its legitimacy in light of Maqasid Syariah. A field study was also conducted through interviews with transgender people in Kuantan, Pahang. The study concluded with some findings, the most important of which are: the importance of observing the general rights that should be given to all without excluding the transgender community which are the rights that Syariah has prescribed in order to preserve the dignity of human being. As for the rights demanded by transgender activists, they are subject to the view of Shariah in terms of being a means to achieve objectives and goals the Shariah aims for.